Propriedades ópticas da alumina anódica porosa e o efeito do guia de onda - Carossi, Lory Cantelli (Universidade Federal de São Carlos, 2015)
Nanoporous anodic alumina films (NAA) may present different behavior to reflectance and photoluminescence techniques, with Fabry-Pérot interferences and waveguide properties. This phenomenon makes possible the use of NAA as transducer signal in optical sensors. In this work, we investigated how the pre-treatment, the number of steps of anodizing, the anodizing electrolyte mode and temperature affect electrochemical characteristics, morphological and optical mainly NAA. As a result, it was noticeable that the realization of electropolishing is necessary for both the NAA with good regularity as to make it possible to obtain a spectrum with the Fabry-Pérot interference. If the fabrication of NAA is done in two steps, it is possible to obtain reflectance spectra and luminescence fringed with better amplitudes, areas and heights. Regarding the anodizing mode, both the NAA anodized in galvanostatic how potentiostatic showed similar morphologies and spectra with fringes, but the interferences were better defined when the galvanostatic mode was performed. Regarding the temperature, it was noticeable that the change of this parameter leads influences the porous oxide thickness. The spectrum of the luminescence and reflectance increasing the electrolyte temperature caused an increase in interference. However, the range and resolution of interference decreased with increasing temperature. The oxide thicknesses were estimated by energy variation (?E), graph slope between order and 1/? and fast Fourier transform (FFT) techniques. The ratio of film thickness and pore diameter (L/dp) was performed to validate the NAA films with better waveguides property. Moreover, the surface composition analysis of NAA films anodized in phosphoric acid, oxalic acid and mixtures thereof by backscattering spectroscopy Rutherford (RBS) was performed. From simulations it was possible to note that the amount of carbon in the porous oxide structure is practically zero, which may indicate that the origin of the luminescence is related to the presence of more centers F.
Keywords: Óxido de alumínio; Aluminum oxide; Thin films - Optical properties; Alumina anódica porosa; Interferências de Fabry-Pérot; Espectroscopia de retroespalhamento de Rutherford; Nanoporous Anodic Alumina; Fabry-Pérot interference; Composition analysis; Filmes finos - Propriedades ópticas; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA